A Decade of Capital Structure Research in Emerging-Market Exporters: A Hybrid Bibliometric and Topic Modeling Review - Sylvia Sandyazmara Devi; Noer Azam Achsani; Anny Ratnawati; Lukytawati Anggraeni (Greenation Research & Yayasan Global Resarch National, 2026)
This review synthesises a decade of research on the capital structure of firms in emerging markets and natural resource exporting economies, focusing on a policy relevant gap, namely how foreign exchange and export proceeds regulation shapes corporate financing decisions. The study draws on 779 records retrieved from Scopus and refined through a PRISMA 2020 protocol into 83 indexed articles and reviews published between 2016 and 2026, supplemented by four regional journal studies. It applies a hybrid design that combines bibliometric performance analysis and science mapping with a structural topic model and a Theory, Context, Characteristics and Methodology synthesis framework. The findings show a young but accelerating field, with annual output rising sharply after 2020 and peaking in 2025, concentrated in China, the United States, India and Indonesia, and dominated by quantitative panel and econometric methods. Thematic mapping reveals four research streams, in which firm level determinants of capital structure dominate, while streams most relevant to resource exporters, such as export intensity, trade finance, foreign exchange and currency retention dynamics, and state ownership, remain thinly populated. These results consolidate a fragmented literature and identify the regulation of export proceeds, exemplified by Indonesia's export proceeds retention policy, as an underresearched determinant of leverage.